Acoustic emission fractal characteristics and mechanical damage mechanism of cemented paste backfill prepared with tantalum niobium mine tailings. (20th October 2020) - Zhao, Kang; Yu, Xiang; Zhu, Shengtang; Yan, Yajing; Zhou, Yun; He, Zhiwei; Song, Yufeng; Huang, Ming
Highlights: The fractal characteristics of the AE correlation different ratios of CPB materials were investigated. Monitoring CPB crack expansion using acoustic emission amplitude fractal features. Fractal dimensions of amplitude were more concentrated in acoustic emission fractal studies. Different of cement tailings ratios CPB have different fractal dimensional values at the time of damage. Abstract: The motivation for this work was to investigate the relationship between the fractal characteristics of the acoustic emission (AE) correlation and the mechanical damage of different ratios of tantalum–niobium tailings CPB materials. The AE parameters of the tailings CPB materials under uniaxial compression were obtained by an AE test. On this basis, the fractal dimensions of the AE parameters were derived, and the change rule of the fractal parameters during the entire specimen damage was obtained by analysis. The results showed that the minimum value of the fractal dimension was generally within a stress-level range of 70% to 90%. While approaching the peak value of the stress, the amplitude fractal dimension displayed an increasing trend. The AE amplitude, event rate, energy rate, and spatial distribution exhibited fractal characteristics. In the investigation of the AE fractal, the fractal dimension of the amplitude was more concentrated, which exhibited that it was more accurate to determine the failure of a cemented paste backfill (CPB). Therefore, the study focused on using the amplitude fractal dimension value to monitor the failure of the CPB. This feature provides a reference for the control of the stability of the surrounding rock by backfilling the goaf with CPB.